Optimizing a Local Resource-Based Business Model for the Gadod Weaving Industry: Increasing Brand Awareness and Customer Engagement - Muhammad Khoirul Umam; Askarno Askarno; Bagaskara Nur Rochmansyah (Publikasi Indonesia, 2025)
The Gadod Weaving Industry in Majalengka, a cultural heritage of high value, faces challenges due to low brand awareness and customer engagement caused by a traditional business model that has not undergone digital transformation. This research aims to optimize a business model based on local resources through collaboration between culture and digital technology to increase brand awareness and customer engagement. This study uses a descriptive qualitative approach with a case study on Gadod Weaving artisans in Nunuk Baru Village. The research findings present a business model design for Tenun Gadod based on local resources, emphasizing community collaboration, cultural storytelling, and digital marketing. The digital campaign